The Effects of ? – Rays on The Optical Constants of ZnS Thin Films (Baghdad Science Journal, 2025)
ZnS thin films were grown onto glass substrates by flash evaporation technique, the effects of ? – rays on the optical constants of ZnS these films were studied. It was found that ? – rays affected all the parameters under investigation.